Strategy For Developing Creative Economy-Based Tourism Villages In Sleman District - Rochmad Bayu Utomo; Ni Luh Gde Ana Pertiwi; Nugraeni; Dina Karista; Ilham Galih Dini Hari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted to determine the existing tourism and creative economy villages that were developed and to formulate a strategy for developing tourism villages based on the creative economy. The data used are primary data in the form of information collected from tourism villages and secondary data in the form of support data from BPS, the Sleman Regency Tourism Office and social media. The techniques used in this study are data exploration, desk analysis, observation and FGD techniques. The results of the study indicate that tourism villages in Sleman Regency develop creative economic potential. In the formulation of a strategy for developing tourism villages based on the creative economy, there are several strengths, weaknesses, opportunities, and threats that are formulated. From the SWOT analysis, several alternative strategies and programs/activities have been produced that can be implemented and attempted to develop the potential of the creative economy in tourism villages in Sleman Regency, namely by improving infrastructure, training and developing human resources, product diversification and innovation and others.